The cascade optimal control of steer by wire system using hardware in the loop simulations - Fachrudin Hunaini; Fressy Nugroho; Purbo Suwandono; Gatot Subiyakto (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper aims to further improve the performance of the control system on the steer by wire (SbW) of vehicle steering system, by presenting the development of optimal control system strategy for lateral motion and yaw motion which is arranged in a cascade so that the vehicle can always be maintained on the desired trajectory. The control system strategy to be developed is fuzzy logic control (FLC) as a lateral motion control and proportional integral derivative (PID) control as a yaw motion control, and to obtain an optimal control system, the modified-quantum particle swarm optimization (MQPSO) optimization method is used. The simulations are carried out using hardware in the loop simulations (HILS) which involve hardware, namely; motor stepper actuator and rotary encoder to determine and monitor the direction of the front wheels which are applied to the vehicle dynamics model in a real time. HILS test results show that vehicle movement can be maintained according to the desired trajectory (double lane change) with an average continues-root mean square (C-RMS) error of 0.015366 for lateral motion and 0.014967 for yaw motion, the average C-RMS error is greater 23.75% for lateral motion and 28.18% for yaw motion against the results of the software in the loop simulations (SILS) test.